Efficacy and safety of fospropofol disodium sedation for same-day bidirectional endoscopy in elderly patients: protocol for a prospective, single-center, randomized, double-blind, non-inferiority trial - Zhe Zhao; Xiaogao Jin; Yong Li; Xiaofeng Wang; Yongchen Cui; Bing Zhang; Yu Kang; Guangming Zhang; Qinjun Chu; Junfeng Zhang (Frontiers Media S.A., 2024)
IntroductionFospropofol disodium is a novel prodrug that has improved pharmacokinetic and pharmacodynamic properties when compared with propofol. This trial aims to compare the efficacy and safety of fospropofol versus propofol sedation for same-day bidirectional endoscopy in elderly patients.Methods and analysisThis is a prospective, single-center, double-blind, randomized, propofol-controlled, non-inferiority trial. A total of 256 patients aged 65 years or older, who are scheduled for same-day bidirectional endoscopy under sedation, will be randomly allocated, in a 1:1 ratio, to either fospropofol group or propofol group (n = 128 in each group). All patients will receive analgesic pre-treatment with sufentanil 5 μg. Two minutes later, an initial bolus dose of fospropofol 6.5 mg/kg or 1.5 mg/kg propofol and supplemental doses of fospropofol 1.6 mg/kg or 0.5 mg/kg propofol will be titrated as needed to achieve target sedation levels during the procedures. The primary outcome is the success rate of same-day bidirectional endoscopy. Secondary outcomes include the time to successful induction of sedation, duration, time to being fully alert, time to patient discharge, endoscopist satisfaction, patient satisfaction, and the top-up frequency and dosage of sedative medications. The safety endpoints consist of adverse events concerning cough reflex, gag reflexes, body movement, muscular tremor, and pain on injection. Sedation-related AEs, including episodes of desaturation, severe desaturation (SpO2 < 90%), hypotension, severe hypotension (decrease in MBP ≥30% of baseline), and bradycardia, will also be recorded. Data will be analyzed on an intention-to-treat basis.DiscussionWe hypothesize that the efficacy and safety of fospropofol sedation for elderly patients undergoing same-visit bidirectional endoscopy will not be inferior to that of propofol. Our findings will potentially provide a new sedation regimen for same-visit bidirectional endoscopy in elderly patients.Clinical Trial Registrationclinicaltrials.gov, identifier NCT02875639